Zur Genese buddhistischer Identität bei westlich sozialisierten Menschen - Gut, Jürgen (Forum Komparative Kasuistik, 2009)
For several years in Western-oriented cultures a growing social criticism at different institutions has been established. The critical questioning of traditional values and practices has led to processes of change, for example, in political parties, trade unions, but also in the Christian churches. In terms of the ecclesiastical and religious matters, it can be said that now on the one hand, many people have left the church, on the other hand, however, a keen and growing interest in spirituality and other faiths, especially in Buddhism has appeared. Meanwhile in Europe, meditation groups, Buddhist monasteries and accordingly-directed lectures and events not only in urban areas have become the norm. This social development is related but not exclusively to the criticism of the churches or the experience of deficits in the local religion but has complex reasons. This paper intends to clarify why western people socialized in the life course turn to Buddhism and identify with its contents. Urged on by the psychology of religion content in this work, does the author intend to contribute a part to the strengthening yet somewhat marginal area of the psychology of religion in order to approach so far often been bracketed psychological question attitudes and support of being human. It should also be pointed out that religion and science are not necessarily mutually exclusive, but that the integration of different perspectives is very fruitful and enlightening.